Innovative Technologies used to Ensure Financial Security - Khozhabaevna, Karlibaeva Raya; Akramovich, Turdiev Odilzhan (European Journal of Life Safety and Stability (2660-9630), 2022)
The article considers an overview of innovative technologies used to ensure financial security. The principle of operation of innovative technologies used to ensure financial security (such as Web application protection, Anti-fraud solutions, Blockchain) and the scope are described in detail.